Maturing thalamocortical functional connectivity across development - Fair, Damien; Bathula, Deepti; Mills, Kathryn L.; Costa Dias, Taciana G.; Blythe, Michael S.; Zhang, Dongyang; Snyder, Abraham Z.; Raichle, Marcus E.; Stevens, Alex A.; Nigg, Joel T.; Nagel, Bonnie J. (Frontiers in Systems Neuroscience, 2010)
Recent years have witnessed a surge of investigations examining functional brain organization using resting-state functional connectivity MRI (rs-fcMRI). To date, this method has been used to examine systems organization in typical and atypical developing populations. While the majority of these investigations have focused on cortical-cortical interactions, cortical-subcortical interactions also mature into adulthood. Innovative work by Zhang et al (Zhang et al., 2008) in adults have identified methods that utilize rs-fcMRI and known thalamo-cortical topographic segregation to identify functional boundaries in the thalamus that are remarkably similar to known thalamic nuclear grouping. However, despite thalamic nuclei being well formed early in development, the developmental trajectory of functional thalamo-cortical relations remains unexplored. Thalamic maps generated by rs-fcMRI are based on functional relationships, and should modify with the dynamic thalamo-cortical changes that occur throughout maturation. To examine this possibility, we employed a strategy as previously described by Zhang et al to a sample of healthy children, adolescents, and adults. We found strengthening functional connectivity of the frontal cortex with dorsal/anterior subdivisions of the thalamus across age groups. Temporal lobe connectivity with ventral/midline/posterior subdivisions of the thalamus weakened with age. Changes in sensory and motor thalamo-cortical interactions were limited. These findings are consistent with known anatomical and physiological cortical-subcortical changes over development. The methods and developmental context provided here will be important for relating how cortical-subcortical interactions relate to models of typically developing behavior and developmental neuropsychiatric disorders.